Expansão da Ocupação Urbana de Gramado: Estudo de Caso da Aplicação de Fotografias Aéreas de Pequeno Formato e SIG - MENDES JÚNIOR, CLÁUDIO WILSON; AYUP-ZOUAIN, RICARDO NORBERTO (Pesquisas em Geociências, 2004)
<!– .p text-align: justify; –> Small format vertical aerial photographs were obtained from non metric cameras on small size airplanes, in 1999, and aimed to update a set of six digital cadastral maps from 1984, in the scale of 1:5,000, covering the urban area of Gramado county, located at the northeast region of the Rio Grande do Sul state, Brazil. The photographs were digitized, stored and georeferenced in a Geographic Information System. Afterwards, the perimeters of the new buildings and the boundaries of the urban area districts were digitized on the digital cadastral maps. The updated data of the cadastral maps were elaborated with the purpose to generate thematic analysis and can´t be used for the accurated measure of the mapped buildings. The poligons of the buildings were topologicaly structured by application of GIS, allowing the automatic generation of a centroid to each mapped building. The database query allowed the evaluation of the total number and the localization of the centroids of the buildings, for both date studied. The recorded data were represented by thematic maps of urban occupation expantion, in the scale of 1:25,000. Based on the data obtained, a 164.6 % increase of the total number of buildings was observed, as well as the occupation expantion towards the SE region of the urban area, caused by the major growth of the secundary sector and the major number of new developments in the meridional urban area, that occurred during the past 15 years. Through the interpretation of geographical data, recommendations were proposed for the urban planning of Gramado county.